2017
DOI: 10.1371/journal.pone.0173523
|View full text |Cite
|
Sign up to set email alerts
|

Safety after extended repeated use of ulipristal acetate for uterine fibroids

Abstract: ObjectiveTo assess long term safety of extended repeated 3-month courses of ulipristal acetate (UPA) 10 mg/day, for up to 8 courses, with focus on endometrial and laboratory safety parameters.MethodsThis long-term, multi-center, open-label cohort, follow up study consisted of up to 8 consecutive 3-month courses of daily UPA 10 mg, each separated by a drug free period of 2 spontaneous menstrual bleeds. Sixty-four pre-menopausal women, with moderate to severe symptomatic uterine myoma(s) and heavy bleeding were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 11 publications
2
42
0
7
Order By: Relevance
“…The safety profile of UPA during single 26,27 and multiple 6,29,30,36 treatment courses was well documented in the four clinical RCTs and no safety issues emerged from physical examination, vital signs or electrocardiograms. The most frequently encountered side effects were hot flushes, breast pain/discomfort and headaches.…”
Section: Can It Be Harmful?mentioning
confidence: 93%
See 4 more Smart Citations
“…The safety profile of UPA during single 26,27 and multiple 6,29,30,36 treatment courses was well documented in the four clinical RCTs and no safety issues emerged from physical examination, vital signs or electrocardiograms. The most frequently encountered side effects were hot flushes, breast pain/discomfort and headaches.…”
Section: Can It Be Harmful?mentioning
confidence: 93%
“…Cystic and stromal changes appear to be reversible and benign, returning to screening levels (±10%) 2 months after completion of therapy in all the PEARL studies . Moreover, in a very recent, extended PEARL III trial, neither atypical hyperplasia nor endometrial adenocarcinoma were reported in women undergoing eight courses of UPA treatment …”
Section: Side Effectsmentioning
confidence: 93%
See 3 more Smart Citations